2015
DOI: 10.1186/s40064-015-0865-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the lymph node ratio for lymph-node-positive breast cancer- is it just a denominator problem?

Abstract: PurposeTo examine the prognostic value of lymph node ratio (LNR) for patients with node-positive breast cancer with varying numbers of minimum nodes removed (>5, > 10 and > 15 total node count).MethodsThis study examined the original histopathological reports of 332 node-positive patients treated in the state of New South Wales (NSW), Australia between 1 April 1995 and 30 September 1995. The LNR was defined as the number of positive lymph nodes (LNs) over the total number of LNs removed. The LNR cutoffs were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…They found that LNR lost its significance in patients with >10 and >15 nodes dissected, perhaps suggesting that LNR holds value only when axillary dissections are inadequate. They concluded that oncologist can be confident that prognosis and decisions on adjuvant therapies can be based on pN classification alone when adequate axillary dissections are performed (>15 nodes) but suggest that pN and LNR should be used on conjunction otherwise [2]. In our study, the mean number of axillary lymph nodes that were examined was [15], which could account for non-significance of our findings.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…They found that LNR lost its significance in patients with >10 and >15 nodes dissected, perhaps suggesting that LNR holds value only when axillary dissections are inadequate. They concluded that oncologist can be confident that prognosis and decisions on adjuvant therapies can be based on pN classification alone when adequate axillary dissections are performed (>15 nodes) but suggest that pN and LNR should be used on conjunction otherwise [2]. In our study, the mean number of axillary lymph nodes that were examined was [15], which could account for non-significance of our findings.…”
Section: Discussionmentioning
confidence: 59%
“…Current nodal staging systems solely use the number of positive axillary LNs, and although this parameter has been shown to be of value, recent literature queries whether additional information on the total number of LNs removed would be of prognostic benefit [13]. This is because data has shown that the chance of finding positive nodes increases with the number of LNs examined, and that under-staging of the axilla can be a result of inadequate dissections [2]. The concept of assessing LN status by ratios was first suggested years ago; a few parameters were developed but the lymph node ratio (LNR) was deemed the most clinically suitable [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Jayasinghe et al (2015),no correlation between ER status and LNR was found. There are, however, some limitations for the value of lymph node ratio evaluation in the present study: data about axillary lymph node status show wide range of number of dissected lymph nodes (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussion:-mentioning
confidence: 81%